Energy storage element

By pressing the electrode body with a minimum pressure of 0.24 MPa and optimizing the pore volume ratio between the negative and positive electrodes, the storage element addresses the issue of increasing resistance in conventional storage elements, achieving improved performance and capacity retention.

JP7665941B2Active Publication Date: 2025-04-22GS YUASA CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020159045
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-23
Publication Date
2025-04-22
Estimated Expiration
2040-09-23

AI Technical Summary

Technical Problem

Conventional electricity storage elements experience an increase in resistance with repeated charging and discharging, leading to a gradual decrease in output performance.

Method used

The electric storage element incorporates an electrode body with a positive electrode and a negative electrode, where at least part of the electrode body is pressed, and the pressure applied in the discharge state is 0.24 MPa or more. Additionally, the ratio of the total pore volume of the negative electrode active material layer to the positive electrode active material layer is greater than 1.0, enhancing electrolyte retention and conductivity.

Benefits of technology

This configuration reduces the rate of resistance increase after charge/discharge cycles, maintaining high capacity retention and improving the overall performance of the storage element.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665941000002
    Figure 0007665941000002
  • Figure 0007665941000003
    Figure 0007665941000003
  • Figure 0007665941000004
    Figure 0007665941000004
Patent Text Reader

Abstract

To provide a power storage element with reduced resistance increase due to repeated charging and discharging.SOLUTION: An aspect of the invention is a power storage element that comprises an electrode body 2 having a positive electrode including a positive electrode active material layer and a negative electrode including a negative electrode active material layer, and an electrolyte, where at least a part of the above electrode body is pressed, where a pressure applied to at least a part of the above electrode body in a discharged state is 0.24 MPa or more, where a ratio of total pore volume of the negative electrode active material layer to total pore volume of the positive electrode active material layer in a portion where the positive electrode active material layer and the negative electrode active material layer are facing each other is greater than 1.0.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an energy storage element. [Background technology]

[0002] Due to their high energy density, non-aqueous electrolyte secondary batteries, typified by lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc. In addition, as electricity storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors, electricity storage elements using electrolytes other than non-aqueous electrolytes, etc. are also widely used.

[0003] A widely used energy storage element is one that includes an electrode assembly in which a positive electrode having a positive electrode active material layer laminated on the surface of a positive electrode substrate and a negative electrode having a negative electrode active material layer laminated on the surface of a negative electrode substrate are stacked together with an electrically insulating separator interposed therebetween. Such an electrode assembly is housed in a container together with an electrolyte to form an energy storage element (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-73761 A [Patent Document 2] JP 2017-69002 A Summary of the Invention [Problem to be solved by the invention]

[0005] Energy storage elements are required to have excellent output performance even after repeated charging and discharging. However, conventional energy storage elements have a disadvantage in that their resistance increases with repeated charging and discharging, resulting in a gradual decrease in output.

[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an energy storage element in which the rate of increase in resistance after charge / discharge cycles is reduced. [Means for solving the problem]

[0007] One embodiment of the present invention is an energy storage element that includes an electrode body having a positive electrode including a positive electrode active material layer and a negative electrode including a negative electrode active material layer, and an electrolyte, wherein at least a portion of the electrode body is in a pressed state, a pressure applied to at least a portion of the electrode body in a discharged state is 0.24 MPa or more, and a ratio of a total pore volume of the negative electrode active material layer to a total pore volume of the positive electrode active material layer in a portion where the positive electrode active material layer and the negative electrode active material layer face each other exceeds 1.0. Effect of the Invention

[0008] According to one embodiment of the present invention, an energy storage element in which the rate of increase in resistance after charge-discharge cycles is reduced can be provided. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is an external perspective view showing an energy storage device according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an energy storage device formed by assembling a plurality of energy storage elements according to one embodiment of the present invention. [Figure 3A] FIG. 3A is a pore distribution curve of the positive electrode active material layer in the secondary battery of Example 1. [Figure 3B] FIG. 3B is a pore distribution curve of the negative electrode active material layer in the secondary battery of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] First, an overview of the energy storage element disclosed in this specification will be described.

[0011] An energy storage element according to one embodiment of the present invention is an energy storage element comprising: an electrode body having a positive electrode including a positive electrode active material layer and a negative electrode including a negative electrode active material layer; and an electrolyte; wherein at least a portion of the electrode body is in a pressed state, a pressure applied to at least a portion of the electrode body in a discharged state is 0.24 MPa or more; and a ratio of a total pore volume of the negative electrode active material layer to a total pore volume of the positive electrode active material layer in a portion where the positive electrode active material layer and the negative electrode active material layer face each other exceeds 1.0.

[0012] In the energy storage element according to one embodiment of the present invention, the resistance increase rate after charge / discharge cycles is reduced. Although the reason is unclear, the following reasons are presumed. First, in the energy storage element, at least a part of the electrode body is pressed with a predetermined pressure or more. Therefore, sufficient conductivity is maintained in the active material layer even after repeated charge / discharge cycles, and it is presumed that the resistance increase rate after charge / discharge cycles is reduced. In addition, in general, in a storage element, when the active material of the positive electrode and the negative electrode expands due to the inflow and outflow of ions accompanying charging and discharging, the pore volume in each active material layer of the positive electrode and the negative electrode becomes smaller, and the electrolyte flows out from each active material layer of the positive electrode and the negative electrode. And when the active material of the positive electrode and the negative electrode shrinks, the pore volume in each active material layer becomes larger, and the electrolyte flows into each active material layer. If the electrolyte does not return sufficiently to the active material layer, a part in the active material layer where the electrolyte is depleted occurs. When charging and discharging are repeated in this state, the current density increases locally around the part in the active material layer where the electrolyte is depleted, promoting the decomposition of the electrolyte, etc., which is thought to cause the active material to deteriorate and cause an increase in resistance. In addition, as the part in the active material layer where the electrolyte is depleted increases with repeated charging and discharging, the reaction area of ​​the active material layer that contributes to charging and discharging decreases, which is thought to cause an increase in resistance. Here, it is generally believed that the ratio of the pore volume with a large pore diameter to the total pore volume is greater in the negative electrode active material layer than in the positive electrode active material layer, so that the electrolyte permeates more slowly due to the capillary phenomenon, and the electrolyte is more likely to run out in the negative electrode active material layer. Therefore, in the energy storage element according to one embodiment of the present invention, the total pore volume of the negative electrode active material layer is increased relative to the total pore volume of the positive electrode active material layer in the portion where the positive electrode active material layer and the negative electrode active material layer face each other, thereby increasing the amount of electrolyte held in the negative electrode active material layer and making it difficult for the electrolyte to run out. For this reason, it is believed that the deterioration associated with the charge / discharge cycle is suppressed and the resistance increase rate after the charge / discharge cycle is reduced in the energy storage element according to one embodiment of the present invention. In addition, when the electrode body is in a pressed state, it is considered that the electrolyte is likely to flow out of the active material layer when the active material expands, and that the electrolyte is unlikely to flow into the active material layer when the active material contracts, so that the electrolyte is likely to run out of each active material layer. However, in the energy storage element according to one aspect of the present invention, by adjusting the ratio of the total pore volumes of the positive electrode active material layer and the negative electrode active material layer as described above, it is difficult for the electrolyte to run out of portions in each active material layer of the positive electrode and the negative electrode, and it is considered that the above effect is achieved. In addition, the energy storage element according to one embodiment of the present invention has an advantage in that the capacity retention rate after charge-discharge cycles is high.

[0013] The "pressure applied to at least a part of the electrode body in a discharged state" is a value measured by the following method. The electric storage element in a discharged state pressed by a pressure member or the like is placed in a compression tester having a load cell. A load sufficiently smaller than the load applied by the pressure member or the like is applied to the electric storage element by the compression tester. In this state, that is, while maintaining the thickness of the electric storage element, the load applied by the pressure member or the like is released, and the change in the load measured by the compression tester is taken as the load applied to the electrode body. The measured load is divided by the area of ​​the surface of the electric storage element to which the load is applied by the pressure member or the like, and the pressure applied to at least a part of the electrode body is taken as the pressure. Note that a load is usually applied to a pair of opposing surfaces of the electric storage element by a pressure member or the like, and the area of ​​only one of the pair of surfaces is taken as the area of ​​the surface to which the load is applied.

[0014] "Discharged state" refers to a completely discharged state, and specifically refers to the following state. First, the storage element is charged at a constant current of 1.0 C until it reaches the charge end voltage during normal use, and then it is charged at a constant voltage for 3 hours to reach a fully charged state. After a 10-minute break, it is discharged at a constant current of 1.0 C until it reaches the lower limit voltage during normal use. This state is called the discharged state. Here, normal use refers to the case where the storage element is used by adopting the charge and discharge conditions recommended or specified for the storage element, and, if a charger for the storage element is provided, the charger is used to use the storage element.

[0015] The "total pore volume (cm)" of the positive electrode active material layer or the negative electrode active material layer in the portion where the positive electrode active material layer and the negative electrode active material layer face each other is defined as 3 ) is the total pore volume (cm) per mass of the positive electrode active material layer or the negative electrode active material layer 3 / g) and the mass (g) of the positive electrode active material layer or the negative electrode active material layer in the portion where the positive electrode active material layer and the negative electrode active material layer face each other. The "total pore volume per mass" of the positive electrode active material layer and the negative electrode active material layer is obtained by measuring the pore volume distribution by mercury intrusion porosimetry. Specifically, an AutoPore9600 is used as a measuring device, and the contact angle of mercury is set to 130° and the surface tension is set to 484 mN / m. The pore diameter range to be measured is set to 20 μm to 0.0055 μm, and the cumulative pore volume in this range is obtained and calculated by dividing the cumulative pore volume by the mass of the active material layer. The total pore volume of the positive electrode active material layer or the negative electrode active material layer in the portion where the positive electrode active material layer and the negative electrode active material layer face each other is calculated from the obtained total pore volume per mass and the mass of the positive electrode active material layer or the negative electrode active material layer in the portion where the positive electrode active material layer and the negative electrode active material layer face each other. The positive electrode active material layer or negative electrode active material layer sample to be used for measuring the pore volume distribution is prepared by the following method. The storage element is discharged at a constant current of 0.05 C to the lower limit voltage for normal use. The storage element is disassembled, and the positive electrode or negative electrode is removed and used as the working electrode, and a single-electrode battery is assembled using metallic Li as the counter electrode. For the positive electrode, the positive electrode potential is 3.0 V vs. Li / Li at a current value of 10 mA per 1 g of positive electrode active material. + The negative electrode is discharged at a constant current until the negative electrode potential reaches 2.0 V vs. Li / Li at a current value of 10 mA per 1 g of negative electrode active material. + The battery is charged at a constant current until the potential of the working electrode reaches a constant value. In this case, charging refers to applying a current to the single-electrode battery so that the potential of the working electrode increases, and discharging refers to applying a current to the single-electrode battery so that the potential decreases. The single-electrode battery is disassembled, the positive electrode or negative electrode is removed, thoroughly washed with dimethyl carbonate, and then dried under reduced pressure at room temperature for 24 hours. The dried positive electrode or negative electrode is cut to a predetermined size (e.g., 2 x 2 cm) and used as a sample for measuring the pore volume distribution. The operations from disassembling the energy storage element to measuring the pore volume distribution are carried out in a dry air atmosphere with a dew point of -40°C or lower.

[0016] The ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer in the portion where the positive electrode active material layer and the negative electrode active material layer face each other is preferably 2.0 or less. When the ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer in the portion where the positive electrode active material layer and the negative electrode active material layer face each other is more than 1.0 and 2.0 or less, the electrolyte is less likely to run out, and the resistance increase rate after charge / discharge cycles is further reduced.

[0017] The BET specific surface area of ​​the negative electrode active material layer in a portion where the positive electrode active material layer and the negative electrode active material layer face each other is 5.5 m 2 When the BET specific surface area of ​​the negative electrode active material layer in the portion where the positive electrode active material layer and the negative electrode active material layer face each other is sufficiently large, the electrolyte solution is more likely to permeate into the negative electrode active material layer, and the resistance increase rate after charge-discharge cycles is further reduced.

[0018] The "BET specific surface area" of the negative electrode active material layer is a value determined from an adsorption isotherm using a nitrogen gas adsorption method. Specifically, the BET specific surface area is measured by the following method. First, the storage element is discharged at a constant current of 0.05C to the lower limit voltage for normal use. The storage element is disassembled, the negative electrode is removed, and a test battery is assembled with metallic Li as the counter electrode. A current of 10mA per 1g of negative electrode active material is applied until the negative electrode potential reaches 2.0V vs. Li / Li. +A constant current discharge is performed until the negative electrode potential reaches 0.5 V. Note that charging refers to applying a current to a single-electrode battery so that the potential of the negative electrode increases. The test battery is disassembled again, and the negative electrode is removed. Dimethyl carbonate is used to thoroughly wash the electrolyte attached to the removed negative electrode, and the negative electrode is dried under reduced pressure at room temperature for 24 hours, and then the negative electrode active material layer is collected and used as the sample to be measured. 1.00 g of powder of the sample to be measured (negative electrode active material layer) is placed in a sample tube for measurement, and the sample is dried under reduced pressure at 120°C for 12 hours to thoroughly remove moisture from the sample to be measured. Next, an adsorption isotherm is measured within the range of relative pressure P / P0 (P0 = approximately 770 mmHg) from 0 to 1 by nitrogen gas adsorption method using liquid nitrogen. Five points are extracted from the region of P / P0 = 0.05 to 0.3 of the obtained adsorption isotherm, and a BET plot is performed, and the BET specific surface area is calculated from the y-intercept and slope of the straight line. The process from dismantling the energy storage element to extracting the negative electrode active material layer is carried out in an argon atmosphere with a dew point of -60°C or lower.

[0019] An energy storage device according to one embodiment of the present invention will be described in detail below.

[0020] <Electricity storage element> The electric storage element according to one embodiment of the present invention includes an electrode assembly having a positive electrode and a negative electrode, and an electrolyte. Hereinafter, a nonaqueous electrolyte secondary battery (hereinafter, simply referred to as a "secondary battery") will be described as an example of an electric storage element. The electrode assembly has a structure in which a positive electrode and a negative electrode are alternately stacked by stacking or rolling with a separator interposed therebetween. The electrode assembly may be a stacked type electrode assembly or a rolled type electrode assembly. The electrode assembly is housed in a container, and the container is filled with a nonaqueous electrolyte. The nonaqueous electrolyte is interposed between the positive electrode and the negative electrode. In addition, the container may be a known metal container, a resin container, or the like that is usually used as a container for a secondary battery.

[0021] (positive electrode) The positive electrode has a positive electrode substrate and a positive electrode active material layer laminated on the positive electrode substrate directly or via an intermediate layer.

[0022] The positive electrode substrate has electrical conductivity. The term "electrically conductive" means that the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 7 "Non-conductive" means that the volume resistivity is 10 7 It means that the resistance is more than Ω·cm. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, etc. or their alloys are used. Among these, aluminum and aluminum alloys are preferred in terms of the balance between potential resistance, high conductivity, and cost. In addition, the positive electrode substrate may be formed in the form of foil, vapor deposition film, etc., and foil is preferred in terms of cost. In other words, aluminum foil is preferred as the positive electrode substrate. In addition, examples of aluminum or aluminum alloys include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H-4160 (2006).

[0023] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, even more preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, the strength of the positive electrode substrate can be increased while increasing the energy density per volume of the secondary battery. The "average thickness" of the positive electrode substrate and the negative electrode substrate described later refers to the value obtained by dividing the punched mass when a substrate of a predetermined area is punched out by the true density and punched area of ​​the substrate.

[0024] The intermediate layer is a coating layer on the surface of the positive electrode substrate, and contains conductive particles such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and can be formed, for example, from a composition containing a resin binder and conductive particles.

[0025] The positive electrode active material layer is formed from a so-called positive electrode mixture containing a positive electrode active material. The positive electrode mixture forming the positive electrode active material layer further contains optional components such as a conductive agent, a binder, a thickener, and a filler as necessary.

[0026] The positive electrode active material can be appropriately selected from known positive electrode active materials. As the positive electrode active material for a lithium ion secondary battery, a material capable of absorbing and releasing lithium ions is usually used. As the positive electrode active material, for example, α-NaFeO 2 Lithium transition metal composite oxides having a crystalline structure, lithium transition metal composite oxides having a spinel crystalline structure, polyanion compounds, chalcogen compounds, sulfur, etc. 2 As an example of a lithium transition metal composite oxide having a crystalline structure, Li[Li x Ni 1-x ]O 2 (0≦x<0.5), Li[Li x Ni γ Co 1-x-γ ]O 2 (0≦x<0.5, 0<γ<1), Li[Li x Co 1-x ]O 2 (0≦x<0.5), Li[Li x Ni γ Mn 1-x-γ ]O 2 (0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co 1-x-γ-β ]O 2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γ Co β Al 1-x-γ-β ]O 2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1). Lithium transition metal composite oxides with spinel crystal structure include Li x Mn 2 O 4 , Li x Ni γ Mn 2-γ O 4 Examples of polyanion compounds include LiFePO 4 , LiMnPO 4 , LiNiPO 4 , LiCoPO 4 , Li 3 V2 (PO 4 ) 3 , Li 2 MnSiO 4 , Li 2 CoPO 4 Examples of the chalcogen compound include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. The atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements.

[0027] The positive electrode active material is preferably a lithium transition metal composite oxide, more preferably a lithium transition metal composite oxide containing nickel, cobalt, and manganese or aluminum, and even more preferably a lithium transition metal composite oxide containing nickel, cobalt, and manganese. This lithium transition metal composite oxide is α-NaFeO 2 It is preferable that the lithium transition metal composite oxide has a type crystal structure. By using such a lithium transition metal composite oxide, it is possible to increase the energy density.

[0028] α-NaFeO 2 As the lithium transition metal composite oxide having a type crystal structure, a compound represented by the following formula (1) is preferable. Li 1+α Me 1-α O 2 (1) In the formula (1), Me is a metal (excluding Li) including Ni, Co, Mn, and Al, and 0≦α<1.

[0029] In formula (1), Me is preferably substantially composed of the three elements Ni, Co, and Mn, or the three elements Ni, Co, and Al, and more preferably composed of the three elements Ni, Co, and Mn, although Me may contain other metals.

[0030] From the viewpoint of achieving a larger electric capacity, the preferred contents (composition ratios) of the constituent elements in the compound represented by formula (1) are as follows. Note that the molar ratio is equal to the atomic ratio.

[0031] In formula (1), the lower limit of the molar ratio of Ni to Me (Ni / Me) is preferably 0.1, and in some cases, 0.2, 0.3, or 0.4 is more preferable. On the other hand, the upper limit of this molar ratio (Ni / Me) is preferably 0.9, and in some cases, 0.8, 0.7, or 0.6 is more preferable.

[0032] In formula (1), the lower limit of the molar ratio of Co to Me (Co / Me) is preferably 0.01, and in some cases, 0.1 or 0.2 is more preferable, while the upper limit of this molar ratio (Co / Me) is preferably 0.5, and in some cases, 0.4 or 0.3 is more preferable.

[0033] In formula (1), the lower limit of the molar ratio of Mn to Me (Mn / Me) may be 0, and in some cases is preferably 0.05, and more preferably 0.1 or 0.2. On the other hand, the upper limit of this molar ratio (Mn / Me) is preferably 0.6, and in some cases is more preferably 0.4 or 0.3.

[0034] In formula (1), the lower limit of the molar ratio of Al to Me (Al / Me) may be 0, and in some cases is preferably 0.01, and more preferably 0.02 or 0.03. On the other hand, the upper limit of this molar ratio (Al / Me) is preferably 0.3, and in some cases is more preferably 0.2 or 0.1.

[0035] In formula (1), the molar ratio of Li to Me (Li / Me), i.e., (1+α) / (1-α), may be 1, and in some cases may be preferably greater than 1.0 (α>0) or greater than or equal to 1.1. On the other hand, the upper limit of this molar ratio (Li / Me) is preferably 1.6, and in some cases may be more preferably 1.4 or 1.2.

[0036] The composition ratio of the lithium transition metal composite oxide refers to the composition ratio when the battery is in a fully discharged state by the following method. First, the storage element (secondary battery) is discharged at a constant current of 0.05 C to the lower limit voltage for normal use. Then, the battery is disassembled, the positive electrode is removed, and a test battery is assembled with metallic Li as the counter electrode. The battery is discharged at a discharge current of 10 mA per 1 g of positive electrode active material until the positive electrode potential reaches 3.0 V vs. Li / Li. + The positive electrode is adjusted to a fully discharged state by discharging at a constant current until the positive electrode reaches a fully discharged state. The device is disassembled again and the positive electrode is removed. Dimethyl carbonate is used to thoroughly wash away the electrolyte adhering to the removed positive electrode, and the device is dried under reduced pressure at room temperature for 24 hours, after which the lithium transition metal composite oxide, the positive electrode active material, is extracted. The extracted lithium transition metal composite oxide is then subjected to measurement. The process from disassembly of the storage element to measurement is carried out in an argon atmosphere with a dew point of -60°C or lower.

[0037] Suitable lithium transition metal composite oxides include, for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 , LiNi 3 / 5 Co 1 / 5 Mn 1 / 5 O 2 , LiNi 1 / 2 Co 1 / 5 Mn 3 / 10 O 2 , LiNi 1 / 2 Co 3 / 10 Mn 1 / 5 O 2 , LiNi 8 / 10 Co 1 / 10 Mn 1 / 10 O 2 , LiNi 0.8 Co 0.15 Al 0.05 O 2 etc. can be mentioned.

[0038] The positive electrode active material may be used alone or in combination of two or more. The content of the lithium transition metal composite oxide in all the positive electrode active materials used is preferably 50% by mass or more, more preferably 70% by mass or more and 100% by mass or less, and even more preferably 80% by mass or more and 100% by mass or less. It is particularly preferable to use a positive electrode active material substantially composed of only the lithium transition metal composite oxide.

[0039] The positive electrode active material is usually a particle. The average particle diameter of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle diameter of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle diameter of the positive electrode active material to the above upper limit or less, the conductivity of the positive electrode active material layer is improved. In addition, when a composite of the positive electrode active material and another material is used, the average particle diameter of the composite is taken as the average particle diameter of the positive electrode active material. The "average particle diameter" means a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle diameter distribution measured by the laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).

[0040] In order to obtain particles with a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. During pulverization, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, an air classifier, etc. are used as necessary for both the dry and wet methods.

[0041] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 95% by mass. By setting the content of the positive electrode active material in the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.

[0042] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. These materials may also be used in combination. For example, a material in which carbon black and CNT are combined may be used. Among these, carbon black is preferable from the viewpoint of electronic conductivity and coatability, and acetylene black is preferable among them.

[0043] The content of the conductive agent in the positive electrode active material layer is preferably 1 mass % or more and 10 mass % or less, and more preferably 3 mass % or more and 9 mass % or less. By setting the content of the conductive agent in the above range, the energy density of the secondary battery can be increased.

[0044] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0045] The content of the binder in the positive electrode active material layer is preferably 1% by mass to 10% by mass, more preferably 2% by mass to 9% by mass, and even more preferably 3% by mass to 6% by mass. By setting the content of the binder in the above range, the positive electrode active material can be stably maintained.

[0046] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be deactivated in advance by methylation or the like. When a thickener is used, the content of the thickener in the positive electrode active material layer can be 0.1% by mass or more and 8% by mass or less, and is usually preferably 5% by mass or less, and more preferably 2% by mass or less. The technology disclosed herein can be preferably implemented in an embodiment in which the positive electrode active material layer does not contain the thickener.

[0047] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. When a filler is used, the content of the filler in the positive electrode active material layer can be 0.1% by mass or more and 8% by mass or less, and is usually preferably 5% by mass or less, and more preferably 2% by mass or less. The technology disclosed herein can be preferably implemented in an embodiment in which the positive electrode active material layer does not contain the filler.

[0048] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.

[0049] The thickness of the positive electrode active material layer is not particularly limited, but is preferably 30 μm to 200 μm, more preferably 50 μm to 150 μm, and even more preferably 70 μm to 120 μm. By setting the thickness of the positive electrode active material layer within the above range, the charge / discharge performance of the secondary battery can be improved.

[0050] The total pore volume of the positive electrode active material layer is 2 cm 3 More than 20cm 3 Less than 3cm is preferable 3 More than 15cm 3 Less than 4cm is preferable. 3 More than 10cm 3 The following is even more preferable. By setting the total pore volume of the positive electrode active material layer within the above range, it is possible to improve the charge / discharge performance of the secondary battery and further reduce the resistance increase rate after charge / discharge cycles, etc. The total pore volume of the positive electrode active material layer can be adjusted by the particle size and specific surface area of ​​the positive electrode active material, the composition, thickness and area of ​​the positive electrode active material layer, whether or not the positive electrode active material layer is pressed during production, and the strength of the press, etc.

[0051] The positive electrode can be produced, for example, by applying a positive electrode mixture paste directly or via an intermediate layer to a positive electrode substrate and drying it. After drying, pressing or the like may be performed as necessary. The positive electrode mixture paste contains each component constituting the positive electrode active material layer, including a positive electrode active material and optional components such as a conductive agent and a binder. The positive electrode mixture paste usually further contains a dispersion medium.

[0052] (Negative electrode) The negative electrode has a negative electrode substrate and a negative electrode active material layer laminated on the negative electrode substrate directly or via an intermediate layer. The intermediate layer may have the same structure as the intermediate layer of the positive electrode.

[0053] The negative electrode substrate can have the same structure as the positive electrode substrate, but the material is a metal such as copper, nickel, stainless steel, nickel-plated steel, or an alloy thereof, and copper or a copper alloy is preferred. That is, the negative electrode substrate is preferably a copper foil. Examples of the copper foil include rolled copper foil and electrolytic copper foil.

[0054] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the secondary battery.

[0055] The negative electrode active material layer is generally formed from a so-called negative electrode mixture containing a negative electrode active material. The negative electrode mixture forming the negative electrode active material layer may contain optional components such as a conductive agent, a binder, a thickener, and a filler as necessary. The optional components such as the conductive agent, the binder, the thickener, and the filler may be the same as those in the positive electrode active material layer.

[0056] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0057] The negative electrode active material can be appropriately selected from known negative electrode active materials. For example, as the negative electrode active material for a lithium ion secondary battery, a material capable of absorbing and releasing lithium ions is usually used. Examples of the negative electrode active material include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li 4 Ti 5 O 12 , LiTiO 2、 TiNb 2 O 7Examples of the material include titanium-containing oxides such as titanium oxide, polyphosphate compounds, silicon carbide, and carbon materials such as graphite and non-graphitic carbon (easily graphitized carbon or non-graphitizable carbon). Among these materials, graphite and non-graphitic carbon are preferred, and graphite is more preferred. In the negative electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.

[0058] "Graphite" refers to a material that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. The "discharged state" of the carbon material refers to a state in which the open circuit voltage is 0.7 V or more in a single-electrode battery using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metal Li (lithium) as a counter electrode. Since the potential of the metal Li counter electrode in the open circuit state is approximately equal to the oxidation-reduction potential of Li, the open circuit voltage in the single-electrode battery is approximately equal to the potential of the negative electrode containing the carbon material relative to the oxidation-reduction potential of Li. In other words, the open circuit voltage of the single-electrode battery being 0.7 V or more means that lithium ions that can be absorbed and released during charging and discharging are sufficiently released from the carbon material, which is the negative electrode active material.

[0059] Examples of graphite include natural graphite and artificial graphite. Artificial graphite is preferred from the viewpoint of availability of a material with stable physical properties.

[0060] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.

[0061] "Non-graphitizable carbon" means the above d 002This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.

[0062] "Graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.

[0063] When the negative electrode active material is in the form of particles, the average particle size of the negative electrode active material can be, for example, 1 nm or more and 100 μm or less. When the negative electrode active material is, for example, a carbon material, the average particle size may be preferably 1 μm or more and 100 μm or less, and more preferably 5 μm or more and 20 μm or less. When the negative electrode active material is a metal, a semi-metal, a metal oxide, a semi-metal oxide, a titanium-containing oxide, a polyphosphate compound, or the like, the average particle size may be preferably 1 nm or more and 1 μm or less. By setting the average particle size of the negative electrode active material to the above lower limit or more, the production or handling of the negative electrode active material becomes easy. By setting the average particle size of the negative electrode active material to the above upper limit or less, the conductivity of the negative electrode active material layer is improved.

[0064] The BET specific surface area of ​​the negative electrode active material layer is 3.0 m 2 / g or more 12m 2 / g or less is preferable, and 4.5m 2 / g over 10m 2 / g or less is more preferable, and 5.5m 2 / g over 9.0m 2 / g or less is more preferable, and 5.6m 2 / g or more 8.0m 2 / g or less is even more preferable. By setting the BET specific surface area of ​​the negative electrode active material layer within the above range, it is possible to improve the charge / discharge performance of the secondary battery. In particular, by setting the BET specific surface area of ​​the negative electrode active material layer to be equal to or greater than the above lower limit, the resistance increase rate after charge / discharge cycles of the secondary battery is further reduced.

[0065] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% by mass to 99% by mass, more preferably 90% by mass to 98% by mass. By setting the content of the negative electrode active material in the above range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.

[0066] The thickness of the negative electrode active material layer is not particularly limited, but is preferably 50 μm to 300 μm, more preferably 100 μm to 250 μm, and even more preferably 140 μm to 200 μm. By making the thickness of the negative electrode active material layer equal to or greater than the lower limit, the charge / discharge performance of the secondary battery can be improved.

[0067] The total pore volume of the negative electrode active material layer is 4 cm 3 More than 24cm 3 Less than 6cm is preferable 3 More than 18cm 3 Less than 8cm is preferable. 3 More than 14cm 3 The following is even more preferable. By setting the total pore volume of the negative electrode active material layer within the above range, it is possible to improve the charge / discharge performance of the secondary battery and further reduce the resistance increase rate after charge / discharge cycles, etc. The total pore volume of the negative electrode active material layer can be adjusted by the particle size and specific surface area of ​​the negative electrode active material, the composition, thickness and area of ​​the negative electrode active material layer, whether or not the negative electrode active material layer is pressed during production, and the strength of the press, etc.

[0068] The negative electrode can be produced, for example, by applying a negative electrode mixture paste directly or via an intermediate layer to a negative electrode substrate and drying it. After drying, pressing or the like may be performed as necessary. The negative electrode mixture paste contains each component constituting the negative electrode active material layer, including a negative electrode active material and optional components such as a conductive agent and a binder. The negative electrode mixture paste usually further contains a dispersion medium.

[0069] (Relationship between positive and negative electrodes) The ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer in the portion where the positive electrode active material layer and the negative electrode active material layer face each other (negative electrode active material layer / positive electrode active material layer) is more than 1.0, preferably 1.05 or more, more preferably 1.1 or more, even more preferably 1.2 or more, and even more preferably 1.3 or more. By making the ratio of the total pore volumes greater than or equal to the lower limit, the electrolyte can be sufficiently allowed to flow into the negative electrode active material layer when the active material contracts, and the resistance increase rate after the charge / discharge cycle of the secondary battery is reduced. On the other hand, the ratio of the total pore volumes (negative electrode active material layer / positive electrode active material layer) may be, for example, 2.5 or less, preferably 2.0 or less, and more preferably 1.9 or less. By setting the ratio of the total pore volumes to be more than the above lower limit or equal to or greater than the lower limit and equal to or less than the above upper limit, it is possible to allow the electrolyte to flow sufficiently into each active material layer when each active material shrinks in both the positive electrode active material layer and the negative electrode active material layer, making it more difficult for the electrolyte to run out, and further reducing the resistance increase rate after charge-discharge cycles of the secondary battery.

[0070] In a preferred embodiment of the present invention, the position of the differential pore volume peak in each pore distribution curve of the positive electrode active material layer and the negative electrode active material layer is determined by: P ) than the peak in the negative electrode active material layer (A N ) is on the larger pore diameter side (see Figs. 3A and 3B). When there are multiple peaks in the differential pore volume, the peak on the largest pore diameter side is used. P The pore diameter corresponding to the peak (A) of the differential pore volume of the negative electrode active material layer is, for example, 0.09 μm or more and 0.15 μm or less. N) is, for example, 0.7 μm or more and 1.7 μm or less. The ratio of the pore volume of pores of 0.1 μm or more to the total pore volume of the negative electrode active material layer is, for example, 50% or more. In another preferred embodiment of the present invention, the positive electrode active material is a lithium transition metal composite oxide, and the negative electrode active material is a carbon material. In the case of a storage element of this type, due to the difference in the ease of occurrence of capillary phenomenon, the negative electrode active material layer is particularly difficult to penetrate with the electrolyte compared to the positive electrode active material layer. Therefore, when a configuration in which the electrolyte easily flows into the negative electrode active material layer is adopted for a storage element of this type, the effect of reducing the resistance increase rate after charge and discharge cycles is remarkably generated. The pore distribution curve of each active material layer is a pore volume distribution measured by the above-mentioned mercury intrusion method.

[0071] (Separator) The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the shape of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of the liquid retention of the nonaqueous electrolyte. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.

[0072] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C in the atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C in the atmosphere. Examples of materials that have a mass loss of a predetermined amount or less when heated include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, barium titanate, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride and barium fluoride; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the secondary battery.

[0073] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.

[0074] (Non-aqueous electrolyte) The nonaqueous electrolyte may be appropriately selected from known nonaqueous electrolytes, and includes a nonaqueous solvent and an electrolyte salt dissolved in the nonaqueous solvent.

[0075] The non-aqueous solvent can be appropriately selected from known non-aqueous solvents. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. As the non-aqueous solvent, those in which some of the hydrogen atoms contained in these compounds are substituted with halogens may be used.

[0076] Examples of cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among these, EC is preferred.

[0077] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among these, DMC and EMC are preferred.

[0078] As the non-aqueous solvent, it is preferable to use at least one of a cyclic carbonate and a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate. By using a cyclic carbonate, it is possible to promote dissociation of the electrolyte salt and improve the ionic conductivity of the non-aqueous electrolyte. By using a chain carbonate, it is possible to keep the viscosity of the non-aqueous electrolyte low. When a cyclic carbonate and a chain carbonate are used in combination, it is preferable that the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is, for example, in the range of 5:95 to 50:50.

[0079] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. Among these, lithium salts are preferred.

[0080] The lithium salt is LiPF 6 , LiPO 2 F 2 , LiBF 4 , LiClO 4 , LiN(SO 2 F) 2 Inorganic lithium salts such as LiSO 3 CF 3 , LiN(SO 2 CF 3 ) 2 , LiN(SO 2 C 2 F 5 ) 2 , LiN(SO 2 CF 3 )(SO 2 C 4 F 9 ), LiC(SO 2 CF 3 ) 3 , LiC(SO 2 C 2 F 5 ) 3 Among these, inorganic lithium salts are preferred, and LiPF 6 is more preferred.

[0081] The content of the electrolyte salt in the non-aqueous electrolyte is 0.1 mol / dm 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less. 3 More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less. 3 More than 1.5mol / dm 3By setting the content of the electrolyte salt within the above range, the ionic conductivity of the nonaqueous electrolyte can be increased.

[0082] The non-aqueous electrolyte may contain an additive. Examples of the additive include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, cyclohexyl benzene, and cyclohexyl benzene. hexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, etc. These additives may be used alone or in combination of two or more.

[0083] The content of the additive contained in the nonaqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive within the above range, it is possible to improve the capacity retention performance or the charge / discharge cycle performance after high-temperature storage, and to further improve safety.

[0084] (Pressing against the electrode body) At least a part of the electrode body is in a pressed state. The lower limit of the pressure applied to at least a part of the electrode body in a discharged state is 0.24 MPa, preferably 0.3 MPa. This allows sufficient conductivity to be maintained in the active material layer even after repeated charging and discharging, and the resistance increase rate of the secondary battery after the charge and discharge cycles can be reduced. In addition, the capacity retention rate of the secondary battery after the charge and discharge cycles also tends to increase.

[0085] Usually, the electrode body stored in the container is pressed from the outside of the container, that is, through the container. Also, usually, the electrode body is pressed in the direction in which the positive electrode, the negative electrode, and the separator are stacked (thickness direction of each layer). That is, the positive electrode active material layer and the negative electrode active material layer are pressed in the direction in which they are crushed in the thickness direction. However, a part of the electrode body (for example, a pair of curved surface parts in a flat wound electrode body) may not be pressed. Also, only a part of the flat part of the laminated electrode body and the flat wound electrode body, for example, only the central part, may be pressed. The upper limit of the pressure in the discharged state is, for example, preferably 3 MPa, more preferably 1 MPa, further preferably 0.6 MPa, and even more preferably 0.4 MPa. When the pressure in the discharged state is equal to or less than the upper limit, the nonaqueous electrolyte is sufficiently flowed into the active material layer, and the resistance increase rate after the charge and discharge cycles of the secondary battery can be further reduced. The pressure in the discharged state may be equal to or more than any of the lower limits and equal to or less than any of the upper limits.

[0086] The pressing (application of a load) to at least a part of the electrode body can be performed, for example, by a pressing member that presses the container from the outside. The pressing member may be a restraining member that restrains the shape of the container. The pressing member (restraining member) is provided so as to sandwich and press the electrode body from both sides in the thickness direction via the container, for example. The pressed surface of the electrode body is in contact with the inner surface of the container directly or via another member. Therefore, the electrode body is pressed by pressing the container. Examples of the pressing member include a restraining band and a metal frame. For example, the metal frame may be configured so that the load can be adjusted by a bolt or the like. In addition, a plurality of secondary batteries (electricity storage elements) may be arranged in the thickness direction of the electrode body, and fixed using a frame or the like in a state in which the plurality of secondary batteries are pressed from both ends in the thickness direction.

[0087] The electric storage element of this embodiment has a reduced resistance increase rate after charge / discharge cycles. In general electric storage elements, when charge / discharge is performed at a high current density, the resistance increase after charge / discharge cycles is usually significant. This is thought to be because the movement of the electrolyte cannot keep up with the high speed charge / discharge, and the electrolyte is particularly likely to be depleted in the active material layer. For this reason, the electric storage element of this embodiment, which is configured so that the electrolyte can sufficiently flow into the active material layer, is suitable for use in applications where charge / discharge is performed at a high current density, such as automotive power sources for electric vehicles (EVs), hybrid vehicles (HEVs), plug-in hybrid vehicles (PHEVs), and the like.

[0088] The shape of the energy storage element (secondary battery) of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a square battery, a flat battery, a coin battery, and a button battery.

[0089] FIG. 1 shows an energy storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51. In the energy storage element 1 of FIG. 1, a pressing member (not shown) or the like may be provided to pressurize the container 3 and the electrode body 2 housed in the container 3 by, for example, sandwiching both sides of the container 3 (usually the front side and the back side in FIG. 1).

[0090] <Method of manufacturing energy storage element> An energy storage element according to one embodiment of the present invention can be manufactured by a manufacturing method including, for example, preparing a positive electrode, preparing a negative electrode, preparing an electrolyte solution, stacking or rolling the positive and negative electrodes with a separator interposed therebetween to form an electrode body in which the positive and negative electrodes are alternately stacked, housing the positive and negative electrodes (electrode body) in a container, injecting the electrolyte solution into the container, sealing the injection port after injection, and attaching a pressure member or the like.

[0091] <Configuration of the power storage device> The energy storage element of the present embodiment can be mounted as an energy storage unit (battery module) formed by assembling a plurality of energy storage elements in a power source for an automobile such as an EV, HEV, or PHEV, a power source for electronic devices such as a personal computer or a communication terminal, or a power storage power source, etc. In this case, it is sufficient that the technology according to one embodiment of the present invention is applied to at least one energy storage element included in the energy storage unit.

[0092] 2 shows an example of an energy storage device 30 in which energy storage units 20, each of which is an assembly of two or more electrically connected energy storage elements 1, are further assembled. The energy storage units 20 or the energy storage device 30 may include a pressing member (not shown) that presses the multiple energy storage elements 1, for example, from the left and right directions in FIG. 2. The energy storage device 30 may include a bus bar (not shown) that electrically connects two or more energy storage elements 1, a bus bar (not shown) that electrically connects two or more energy storage units 20, and the like. The energy storage unit 20 or the energy storage device 30 may include a status monitoring device (not shown) that monitors the status of one or more energy storage elements.

[0093] <Other embodiments> The present invention is not limited to the above-described embodiments, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.

[0094] In the above embodiment, the case where the storage element is used as a chargeable and dischargeable non-aqueous electrolyte secondary battery (e.g., a lithium ion secondary battery) has been described, but the type, shape, size, capacity, etc. of the storage element are arbitrary. The storage element of the present invention can also be applied to various non-aqueous electrolyte secondary batteries, electric double layer capacitors, lithium ion capacitors, and other capacitors. The storage element of the present invention can also be applied to storage elements in which the electrolyte is an electrolyte other than a non-aqueous electrolyte. EXAMPLES

[0095] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. The total pore volume and pore diameters corresponding to the peaks of the differential pore volume of the positive and negative active material layers, the BET specific surface area and the ratio of the volume of pores of 0.1 μm or more to the total pore volume (the ratio of the volume of pores of 0.1 μm or more) of the negative active material layer, and the average particle size of the negative active material are values ​​measured by the above-mentioned methods. In the following, the total pore volume of the positive and negative active material layers is the total pore volume in the portion where the positive and negative active material layers face each other, and the BET specific surface area of ​​the negative active material layer is the BET specific surface area in the portion where the positive and negative active material layers face each other.

[0096] [Example 1] (Preparation of positive electrode) Positive electrode active material LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 A positive electrode mixture paste was prepared using acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersion medium. The mass ratio of the positive electrode active material, AB, and PVDF was 93:3.5:3.5 (solid content conversion). The positive electrode mixture paste was applied to both sides of aluminum foil as a positive electrode substrate and dried. Then, roll pressing was performed to obtain a positive electrode. The total pore volume of the positive electrode active material layer was 7.92 cm. 3 The pore diameter corresponding to the peak of the differential pore volume of the positive electrode active material layer was 0.12 μm.

[0097] (Preparation of negative electrode) A negative electrode mixture paste was prepared using graphite A (average particle size 9.0 μm) as the negative electrode active material, styrene-butadiene rubber (SBR) as the binder, carboxymethyl cellulose (CMC) as the thickener, and water as the dispersion medium. The mass ratio of the negative electrode active material, SBR, and CMC was 97.5:1.5:1 (solid content conversion). The negative electrode mixture paste was applied to both sides of copper foil as the negative electrode substrate and dried. Then, roll pressing was performed to obtain a negative electrode. The total pore volume of the negative electrode active material layer was 9.10 cm 3 The BET specific surface area of ​​the negative electrode active material layer was 5.2 m 2 / g. The pore diameter corresponding to the peak of the differential pore volume of the negative electrode active material layer was 0.83 μm. The ratio of the pore volume of pores of 0.1 μm or more to the total pore volume of the negative electrode active material layer was 65%. The ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer was 1.15.

[0098] (Non-aqueous electrolyte) A mixture of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 30:70 was added to a solvent with a salt concentration of 1.2 mol / dm 3 LiPF 6 was dissolved to obtain a non-aqueous electrolyte solution.

[0099] (Separator) The separator used was a microporous polyolefin film.

[0100] (Battery Assembly) A wound electrode body was obtained using the positive electrode, negative electrode, and separator. The electrode body was placed in a square container, and a nonaqueous electrolyte was poured in and sealed. A pressure member was attached, and the electrode body was pressed at 0.48 MPa in a discharged state from both sides of the container by the pressure member, to obtain a secondary battery (electric storage element) of Example 1. The pore distribution curve of the positive electrode active material layer in the secondary battery of Example 1 is shown in FIG. 3A, and the pore distribution curve of the negative electrode active material layer is shown in FIG. 3B.

[0101] [Example 2] The negative electrode active material was changed to graphite B (average particle diameter 10 μm) and the total pore volume was increased to 9.06 cm 3 , BET specific surface area is 4.9m 2 A secondary battery of Example 2 was obtained in the same manner as in Example 1, except that a negative electrode active material layer was formed having a pore size of 1.03 μm / g, a pore size corresponding to the peak of the differential pore volume of 1.03 μm, and a ratio of pore volume of pores of 0.1 μm or more to the total pore volume of 61%. The ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer in the secondary battery of Example 2 was 1.14.

[0102] [Example 3] The coating weight of the positive electrode active material layer was changed to a total pore volume of 7.42 cm 3 The positive electrode active material layer had a pore size of 0.12 μm, which corresponds to the peak of the differential pore volume. The negative electrode active material was changed to graphite B (average particle size 10 μm). Furthermore, the pressing pressure of the roll press was changed to increase the total pore volume to 9.96 cm. 3 , BET specific surface area is 5.7m 2 A secondary battery of Example 3 was obtained in the same manner as in Example 1, except that a negative electrode active material layer was formed having a pore size of 1.57 μm / g, a pore size corresponding to the peak of the differential pore volume of 1.57 μm, and the proportion of pore volume of pores of 0.1 μm or more in the total pore volume was 73%, and the pressure of the pressing member was changed to 0.36 MPa. The ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer in the secondary battery of Example 3 was 1.34.

[0103] [Example 4] The positive electrode active material is LiNi 1 / 2 Co 3 / 10 Mn 1 / 5 O 2 The total pore volume was changed to 7.95 cm3 by changing the coating weight. 3 The positive electrode active material layer had a pore size of 0.12 μm, which corresponds to the peak of the differential pore volume. The total pore volume was increased to 9.14 cm by changing the coating weight. 3 , BET specific surface area is 5.2m 2 A secondary battery of Example 4 was obtained in the same manner as in Example 1, except that a negative electrode active material layer was formed having a pore size of 0.75 μm / g, a pore size corresponding to the peak of the differential pore volume of 0.83 μm, and the proportion of pore volume of pores of 0.1 μm or more in the total pore volume was 65%. The ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer in the secondary battery of Example 4 was 1.15.

[0104] [Example 5] The total pore volume was increased to 6.14 cm by changing the coating weight. 3The positive electrode active material layer had a pore size of 0.12 μm, which corresponds to the peak of the differential pore volume. The negative electrode active material was changed to graphite B (average particle size 10 μm), the mass ratio of the negative electrode active material, SBR and CMC was changed to 98:1:1 (solid content conversion), and the coating weight was further changed to a total pore volume of 11.55 cm. 3 , BET specific surface area is 5.7m 2 A secondary battery of Example 5 was obtained in the same manner as in Example 1, except that a negative electrode active material layer was formed having a pore size of 1.29 μm / g, a pore size corresponding to the peak of the differential pore volume of 1.29 μm, and the proportion of pore volume of pores of 0.1 μm or more to the total pore volume was 68%, and the pressure of the pressing member was changed to 0.36 MPa. The ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer in the secondary battery of Example 5 was 1.88.

[0105] [Comparative Example 1] The negative electrode active material was changed to graphite C (average particle diameter 6.6 μm) and the total pore volume was increased to 7.89 cm 3 , BET specific surface area is 5.1m 2 A secondary battery of Comparative Example 1 was obtained in the same manner as in Example 1, except that a negative electrode active material layer was formed having a pore size of 0.1 μm / g, a pore size corresponding to the peak of the differential pore volume of 0.53 μm, and the proportion of pore volume of pores of 0.1 μm or more in the total pore volume was 60%. The ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer in the secondary battery of Comparative Example 1 was 1.00.

[0106] [Comparative Example 2] The total pore volume was increased to 7.91 cm by changing the coating weight. 3 The positive electrode active material layer had a pore size of 0.12 μm, which corresponds to the peak of the differential pore volume. When flake graphite was further mixed into the negative electrode mixture paste, the mass ratio of the negative electrode active material, SBR, CMC, and flake graphite was 87.5:1.5:1:10 (solid content conversion), and the total pore volume was 7.81 cm 3 , BET specific surface area is 5.0m 2A secondary battery of Comparative Example 2 was obtained in the same manner as in Example 1, except that a negative electrode active material layer was formed having a pore size of 0.72 μm / g, a pore size corresponding to the peak of the differential pore volume of 0.82 μm, and the proportion of pore volume of pores of 0.1 μm or more in the total pore volume was 64%. The ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer in the secondary battery of Comparative Example 2 was 0.99.

[0107] [Comparative Example 3] The positive electrode active material is LiNi 1 / 2 Co 3 / 10 Mn 1 / 5 O 2 The conductive agent was changed to furnace black, and the coating weight was changed to a total pore volume of 9.44 cm 3 The positive electrode active material layer had a pore size of 0.18 μm, which corresponds to the peak of the differential pore volume. The total pore volume was increased to 9.14 cm by changing the coating weight. 3 , BET specific surface area is 5.2m 2 A secondary battery of Comparative Example 3 was obtained in the same manner as in Example 1, except that a negative electrode active material layer was formed having a pore size of 0.75 μm / g, a pore size corresponding to the peak of the differential pore volume of 0.83 μm, and the proportion of pore volume of pores of 0.1 μm or more in the total pore volume was 65%. The ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer in the secondary battery of Comparative Example 3 was 0.97.

[0108] [Comparative Example 4] The total pore volume was increased to 6.53 cm by changing the coating weight. 3 The mass ratio of the negative active material, SBR, and CMC was changed to 97:2:1 (solid content equivalent), and the coating weight was further changed to 6.52 cm. 3 , BET specific surface area is 5.2m 2A secondary battery of Comparative Example 4 was obtained in the same manner as in Example 1, except that a negative electrode active material layer was formed in which the pore size was 0.77 μm / g, the pore size corresponding to the peak of the differential pore volume was 0.77 μm, and the proportion of pore volume of pores of 0.1 μm or more to the total pore volume was 58%, and no pressing member was attached (no pressure was applied to the electrode body). The ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer in the secondary battery of Comparative Example 4 was 1.00.

[0109] [Comparative Example 5] The total pore volume was increased to 5.97 cm by changing the coating weight. 3 The positive electrode active material layer had a pore size of 0.12 μm, which corresponds to the peak of the differential pore volume. The total pore volume was increased to 12.70 cm by changing the pressing pressure of the roll press and the coating weight. 3 , BET specific surface area is 5.2m 2 A secondary battery of Comparative Example 5 was obtained in the same manner as in Example 1, except that a negative electrode active material layer was formed having a pore size of 1.10 μm / g, a pore size corresponding to the peak of the differential pore volume of 1.10 μm, and the proportion of pore volume of pores of 0.1 μm or more in the total pore volume was 62%, and the pressing pressure by the pressing member was changed to 0.19 MPa. The ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer in the secondary battery of Comparative Example 5 was 2.12.

[0110] [evaluation] (Initial Resistance) Each of the obtained secondary batteries was charged at a constant current of 1.0 C at 25° C. to bring the SOC (State of Charge) to 50%, and then discharged for 30 seconds at currents of 0.2 C, 0.5 C, or 1.0 C at −10° C. The relationship between the current and the voltage 10 seconds after the start of discharge was plotted at each discharge current, and the DC resistance was calculated from the slope of the straight line obtained by plotting the three points, which was used as the initial resistance.

[0111] (Charge-discharge cycle test) Next, the following charge-discharge cycle test was performed. The battery was charged at a constant current of 8 C at 60° C. with a charge cut-off voltage of 4.10 V. Thereafter, without a pause, the battery was discharged at a constant current of 8 C with a lower limit voltage of 2.50 V. This charge-discharge cycle was repeated 6000 times.

[0112] (Rate of increase in resistance) After the charge-discharge cycle test, the DC resistance of each secondary battery was measured in the same manner as in the above "initial resistance" and was taken as the resistance after the charge-discharge cycle test. The resistance increase rate after the charge-discharge cycle test was calculated by dividing the difference between the resistance after the charge-discharge cycle test and the initial resistance by the initial resistance. The results are shown in Table 1.

[0113] (Capacity maintenance rate) In the charge-discharge cycle test, the discharge capacity at the 6000th cycle relative to the discharge capacity at the 1st cycle was calculated as the capacity retention rate. The results are shown in Table 1.

[0114] [Table 1]

[0115] As shown in Table 1, in the secondary batteries of Examples 1 to 5 in which the pressure applied to at least a part of the electrode body in a discharged state is 0.24 MPa or more and the ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer in the portion where the positive electrode active material layer and the negative electrode active material layer face each other is more than 1.0, the resistance increase rate after the charge-discharge cycle was low. In addition, in the secondary batteries of each of these Examples, the capacity retention rate after the charge-discharge cycle was sufficiently high. Furthermore, as in the secondary batteries of Examples 3 and 5, it was confirmed that the resistance increase rate after the charge-discharge cycle tends to be lower by increasing the ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer. In addition, as in the secondary batteries of Examples 3 and 5, in which the BET specific surface area of ​​the negative electrode active material layer is 5.5 m 2 / g, it was confirmed that the resistance increase rate after charge-discharge cycling tends to be lower.

[0116] On the other hand, when the ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer in the portion where the positive electrode active material layer and the negative electrode active material layer face each other was 1.0 or less as in the secondary batteries of Comparative Examples 1 to 4, and when the pressure applied to at least a part of the electrode body in the discharged state was less than 0.24 MPa as in the secondary batteries of Comparative Examples 4 and 5, the resistance increase rate after the charge-discharge cycle was high. [Industrial Applicability]

[0117] The present invention can be applied to electronic devices such as personal computers and communication terminals, and to energy storage elements used as power sources for automobiles and the like. [Explanation of symbols]

[0118] 1 Energy storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. The battery includes an electrode assembly having a positive electrode including a positive electrode active material layer and a negative electrode including a negative electrode active material layer, and an electrolyte solution; At least a portion of the electrode body is pressed, and a pressure applied to at least a portion of the electrode body in a discharge state is 0.24 MPa or more and 0.4 MPa or less; A secondary battery in which the ratio of the total pore volume of the negative electrode active material layer to the total pore volume of the positive electrode active material layer in a portion where the positive electrode active material layer and the negative electrode active material layer face each other is greater than 1.

0.

2. 2. The secondary battery according to claim 1, wherein a ratio of a total pore volume of the negative electrode active material layer to a total pore volume of the positive electrode active material layer in a portion where the positive electrode active material layer and the negative electrode active material layer face each other is 2.0 or less.

3. The BET specific surface area of ​​the negative electrode active material layer in a portion where the positive electrode active material layer and the negative electrode active material layer face each other is 5.5 m 2 The secondary battery according to claim 1 or 2, wherein the R2 is greater than 1 / g.

Citation Information

Patent Citations

  • Lithium secondary battery

    JP2001093577A

  • Power storage element

    JP2013073761A

  • Nonaqueous electrolyte storage element

    JP2014130717A

  • Nonaqueous electrolyte secondary battery

    JP2016105349A

  • Power storage device

    JP2017069002A